A case study on economic dimension of Occupational Safety and Health: equipment capital cost analysis - Masitah, Mahram (2025)
Occupational Safety and Health (OSH) is an integral aspect of ensuring worker safety, operational efficiency, and economic sustainability in process industries. This study investigates the economic implications of safety investments by analyzing equipment capital costs for heat exchangers and compressors used in the 2-ethylhexanol production process. The research employs a structured methodology encompassing Hazard and Operability (HAZOP) analysis, equipment sizing, and cost estimation using the CAPCOST software, with cost adjustments based on the Chemical Engineering Plant Cost Index (CEPCI). The study begins by identifying potential hazards associated with heat exchangers and compressors through a predefined HAZOP framework, which is further enhanced by recommendations for safety measures. Deviations in temperature, pressure, and operational performance are meticulously assessed, and specific safeguards, including temperature sensors, pressure relief valves, and predictive maintenance practices, are proposed. These safeguards aim to mitigate the identified risks, such as thermal expansion, over-pressurization, and fouling, which could lead to catastrophic equipment failure. The economic dimension of safety investments is explored through a detailed preliminary Cost- Benefit Analysis (CBA), which evaluates the financial feasibility of the proposed safeguards. The analysis compares the total capital costs, including direct and indirect expenditures, against the potential cost savings from reduced risks and improved operational efficiency. The findings reveal that proactive safety investments yield significant long-term benefits, such as minimized downtime, reduced accident-related costs, and enhanced process reliability. Furthermore, the study highlights the importance of aligning safety measures with industry standards and incorporating expert validation through Focus Group Discussions (FGD). These discussions with experienced professionals provide critical insights into the practicality and effectiveness of the proposed safety enhancements. This research contributes to the broader understanding of the economic justification for OSH investments in the chemical process industry. By demonstrating the value of comprehensive safety measures, it underscores the need for a balanced approach that prioritizes both worker well-being and organizational profitability. The findings not only serve as a guide for future safety investments but also promote a culture of safety and sustainability within high-risk industrial sectors.